Advanced six degrees of freedom aerospace simulation and analysis - Zipfel, Peter H.; American Institute of Aeronautics and Astronautics (Virginia : American Institute of Aeronautics and Astronautics, 2005)
In 20 labs, we eill learn the formulation of six degrees of freedom equations of motions over the rotating elliptical Earth, study the aerodynamics, propulsion and flight controls of a hypersonic ascent vehicle, insert a transfer vehicle into orbit, and release an interceptor that rendezvous with a space station or intercepts a satellite
System requirements : IBM compatible PC, Microsoft Internet explorer (version 6), Microsoft Visual C++ (ver. 6 or 7) ; CADAC-Studio for plotting (apply for free CD at www.aiaa.org, search for CADAC)
Keywords: Space shuttles; Astronautics; Aeronautics